Effect of Heat on Velocity and Heat Transfer Coefficient of the Fluid in a Pipe with a Laminar Flow - Poudel, Madhav Prasad (Himalayan Journal of Applied Science and Engineering, 2022)
The study of flow of liquids in a circular pipe has been studied for a long time. The theoretical and numerical analysis of viscous fluid is very important in the field of physics, engineering and even in medicine. In any fluid flow, the Napier-Stokes equation are very important to study the nature of flow. On the basis of Reynold number, the flow is either classified as laminar or turbulent. When the heat is supplied to a circular pipe with a liquid having laminar flow, the velocity, rate of flow of volume, temperature gradient, etc. are changed. This study aims to investigate the change in velocity, pressure drop, frictional factor and temperature distribution in the thermal layer across the liquid in the laminar flow. Various boundary conditions are assumed and the conservation of energy, momentum are also considered.